Comparison of Sol Gel and Dehydration Magnesium Oxide (MgO) as a Catalyst in Michael Addition Reaction - Yusoff, Hanis Mohd; Hazwani, Nuur Ul; Hassan, Norhafiefa; Izwani, Fatin (International Journal of Integrated Engineering, 2015)
Magnesium oxide (MgO) was prepared by dehydration of magnesium carbonate method and sol gel method. The prepared MgO powders were calcined at the temperature of 200, 400, 600, and 800 ÂºC for two hours. Then, the samples were characterized by using fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscope (SEM). In order to investigate the prepared MgO, the samples were applied in Michael addition reaction to produce diethyl 2-(3-oxo-1,3-dipehnylpropyl) malonate. The highest percentage yield of 94% was obtained from MgO pepared from sol gel method and calcined at 800 ÂºC.